Modelagem virtual do Museu Ferroviário Regional de Bauru - Figueiredo, Carlos Filipe Mello de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The main objective of this project is to expand the Regional Railroad Museum of Bauru into a virtual space with the Three-dimensional modeling software, called Blender. Museums are great repositories of histories contained on the collections exposed, which lot of times there is not an opportunity to get to know one due its distance. The main goal to build a virtual museum is to enable access by internet, permitting the visitor a possibility to visit it and study it without the necessity to dislocate physically

O objetivo principal deste trabalho é expandir o Museu Ferroviário Regional de Bauru para um espaço virtual com o programa de modelagem tridimensional, o Blender. Os museus são grandes repositórios de Histórias contidas nos acervos expostos, e muitas vezes não se tem a oportunidade de conhecer devido a distancia. Construir um museu virtual tem o principal propósito de possibilitar acesso por meio da internet, permitindo com que o visitante tenha a possibilidade de realizar visitas e estudos do museu, sem ter a necessidade de se deslocar fisicamente
Keywords: Museus digitais; Arquitetura de museus; Museus historicos - Bauru (SP); Museums